Nurses' perception on patient safety culture in critical care area at a tertiary hospital in Pahang, Malaysia - Mohamed Ludin, Salizar; Bajuri, Nur Ainun Athirah (Lincoln University College, Malaysia, 2020)
Patient safety culture is important in measuring the quality of health care. There is a need for the establishment of patient safety culture in hospitals as it is one of the global issues that requires attention. Issues such as medication errors are the third leading cause of death in the US and approximately one in ten patients have been reported being harmed while receiving hospital treatment. Adverse events such as bed falls, adverse drug effects, infections, work overload and absenteeism have become the matters of risk for the patient’s safety. Nevertheless, research that is related to patient safety were less studied in the healthcare area especially dealing with ill patients in the Intensive Care Unit (ICU).